Neutralization effect of plasma from vaccinated COVID-19 convalescents on SARS-CoV-2 Omicron variants - Xie, Yudi; Liu, Lei; Wang, Jue; Zheng, Yaqiong; Luo, Chen; Ni, Wenxu; He, Zhihang; Zhao, Xin; Liu, Yan; He, Yingyu; Zheng, Shangen; Li, Ling; et al. (Frontiers in Immunology, 2022)
Background: COVID-19 has caused a global pandemic and the death toll is increasing. With the coronavirus continuously mutating, Omicron has replaced Delta as the most widely reported variant in the world. Studies have shown that the plasma of some vaccinated people does not neutralize the Omicron variant. However, further studies are needed to determine whether plasma neutralizes Omicron after one- or two-dose vaccine in patients who have recovered from infection with the original strain. Methods: The pseudovirus neutralization assays were performed on 64 plasma samples of convalescent COVID-19 patients, which were divided into pre-vaccination group, one-dose vaccinated group and two-dose vaccinated group. Results: In the three groups, there were significant reductions of sera neutralizing activity from WT to Delta variant (B.1.617.2), and from WT to Omicron variant (B.1.1.529) (ps＜0.001), but the difference between Delta and Omicron variants were not significant (p＞0.05). The average neutralization of the Omicron variant showed a significant difference between pre-vaccination and two-dose vaccinated convalescent individuals (p＜0.01). Conclusions: Among the 64 plasma samples of COVID-19 convalescents, whether vaccinated or not, Omicron (B.1.1.529) escaped the neutralizing antibodies, with a significantly decreased neutralization activity compared to WT. And two-dose of vaccine could significantly raise the average neutralization of Omicron in convalescent individuals.